2017
DOI: 10.1253/circj.cj-16-0870
|View full text |Cite
|
Sign up to set email alerts
|

Neurohumoral and Endothelial Responses to Heated Water-Based Exercise in Resistant Hypertensive Patients

Abstract: 155 patients with a diagnosis of resistant HT were screneed for the HEx trial in the HT outpatient clinic of the University Hospital of São Paulo, Brasil. We excluded 111 patients, with the remaining 44 patients included in the present study. They were sedentary, aged between 40 and 65 years, diagnosed as affected by resistant HT for more than 5 years, and who in the previous 6 months had unchanged and regular use of at least 3 optimally dosed antihypertensive drugs, including a diuretic, and displayed office … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 38 publications
0
46
0
Order By: Relevance
“… 35 This downward trend in ABPM was also observed in subsequent studies with heated water-based exercise training. 36 38 A 12-week heated water-based exercise training 37 composed of 60-minute exercise sessions of callisthenic exercises against water resistance and walking, three times per week, decreased systolic and diastolic ABPM, respectively, in the 24-hour period by 19.5±11.0 mmHg and 11.1±3.1 mmHg, daytime by 22.3±12.6 mmHg and 13.0±3.6 mmHg, and nighttime by 17.4±9.1 mmHg and 8.5±2.1 mmHg. The authors associated the greater magnitude of the blood pressure reductions, compared with the land-based exercise program, 35 with the immersion in water at a temperature of 30°C–32°C.…”
Section: Exercise For the Management Of Resistant Hypertensionmentioning
confidence: 99%
“… 35 This downward trend in ABPM was also observed in subsequent studies with heated water-based exercise training. 36 38 A 12-week heated water-based exercise training 37 composed of 60-minute exercise sessions of callisthenic exercises against water resistance and walking, three times per week, decreased systolic and diastolic ABPM, respectively, in the 24-hour period by 19.5±11.0 mmHg and 11.1±3.1 mmHg, daytime by 22.3±12.6 mmHg and 13.0±3.6 mmHg, and nighttime by 17.4±9.1 mmHg and 8.5±2.1 mmHg. The authors associated the greater magnitude of the blood pressure reductions, compared with the land-based exercise program, 35 with the immersion in water at a temperature of 30°C–32°C.…”
Section: Exercise For the Management Of Resistant Hypertensionmentioning
confidence: 99%
“…The trials involved 452 subjects in total: 251 subjects in the exercise group and 201 subjects in the control group. Thirteen trials [27][28][29][31][32][33][34][35][36][37][38][39] reported the number of subjects by sex. In total, those trials involved 60 men (14.6%) and 352 women (85.4%).…”
Section: Trial Characteristicsmentioning
confidence: 99%
“…In total, those trials involved 60 men (14.6%) and 352 women (85.4%). Thirteen trials [27][28][29][31][32][33][34][35][36][37][38][39] reported the mean age of subjects, which ranged from 45 to 72 years (median 55 years of age). Seven trials 27,33,35,36,38,39 were conducted on hypertensive subjects.…”
Section: Trial Characteristicsmentioning
confidence: 99%
“…The physical properties of water, such as the hydrostatic pressure, are responsible for facilitating venous return, which stimulates baroreceptors to trigger the increase in cardiac filling volume and stroke volume, reflexively reducing heart rate and BP [6,[35][36][37]. In addition, heated water ranging from 30 to 32°C triggers a reduction in peripheral vascular resistance due to dilatation of arterioles [6,18,38].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, HEx reduces circulating levels of adrenergic neurotransmitters epinephrine and norepinephrine, renin and endothelin-1, as well as increases circulating levels of nitric oxide, which may results in reduced peripheral vascular resistance [38]. Regarding neurohumoral regulation, the improved renal system undergoes inhibition of renin-angiotensinaldosterone system, increases factors that excrete sodium (atrial natriuretic peptide), and favors diuresis, which reduce blood volume [9,18,38]. Other hypothesis is that there are improvements in sympathomodulatory and arterial baroreceptors after HEx, which reduce BP.…”
Section: Discussionmentioning
confidence: 99%